Identification Chemical Compounds of Cymbopogon nardus (L.) Rendle Essential Oil Using Gas Chromatography and Mass Spectrophotometry (GC-MS) - Marisa Tamara Sari; Yelfi Anwar; Andrianopsyah Mas Jaya Putra (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The fragrant Citronella oil derived from Cymbopogon nardus (L.) Rendle has many benefits, one of which is as an antibacterial. This research aims to identify the chemical compounds present in the essential oil Citronella obtained from a local distillery in Anding Village, Suliki District, Gunung Mas 50 Kota Regency, Province West Sumatra. The essential oil Citronella was identified using Gas Chromatography-Mass Spectrophotometry (GC-MS) at the BRIN (National Research and Innovation Agency) chemistry laboratory in Serpong, South Tangerang, Banten. The results showed that the essential oil Citronella met the requirements of SNI 06-3953-1995, and after being identified with GC-MS, 39 chemical compounds were found, with 3 compounds having high concentrations in the essential oil: Citronellal (24.57%), Citronellol (11.69%), and Geraniol (15.59%).